2017
DOI: 10.1016/j.ejim.2017.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Technological aided assessment of the acutely ill patient – The case of postoperative complications

Abstract: Surgical interventions come with complications and highly reported mortality after major surgery. The mortality may be a result of delayed detection of severe complications due to lower monitoring frequency in the general wards. Several studies have shown that continuous monitoring is superior to the manually intermittent recorded monitoring in terms of detecting abnormal physiological signs. Hopefully improved observations may result in earlier detection and clinical intervention. This narrative review will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…During these long hours without observation patients might deteriorate without detection, as suggested by previous studies where 90% of cases with desaturation <90% lasting longer than 60 minutes went undetected by routine ward rounds. Continuous monitoring may thus improve patient care by increasing the sensitivity and predictive accuracy of the detected deteriorations as well as detecting them sooner …”
Section: Introductionmentioning
confidence: 99%
“…During these long hours without observation patients might deteriorate without detection, as suggested by previous studies where 90% of cases with desaturation <90% lasting longer than 60 minutes went undetected by routine ward rounds. Continuous monitoring may thus improve patient care by increasing the sensitivity and predictive accuracy of the detected deteriorations as well as detecting them sooner …”
Section: Introductionmentioning
confidence: 99%
“…Limited data have been published regarding the clinical application of continuous multi-parameter wireless monitoring in hospitalised patients outside the ICU setting [17,28], however a number of studies are currently ongoing. Studies have been conducted in different settings across specialties, but we were unable to find studies specifically in patients admitted with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the important question of how we alert clinical staff about adverse physiologic deviations to ensure timely interventions in a way where alarms do not cause alarm fatigue and other causes for unresponsiveness to alerts. 7 This should be an important research objective, if results such as the ones found by Liem et al are to alter clinical practice.…”
Section: Implications For Postoperative Clinical Monitoringmentioning
confidence: 98%
“…1 However, from a physiologic standpoint, there is no reason to assume that deviations only occur in these units. 7 The literature suggests a paucity in our understanding of complications occurring in general wards and especially after discharge. 8 Future studies should also aim outside these highly specialized settings when caring for patients at high risk of cardiovascular and other surgical complications.…”
Section: Implications For Postoperative Clinical Monitoringmentioning
confidence: 99%